Perbedaan Motivasi Belajar Antara Siswa Laki-Laki dan Siswa Perempuan - Winda Oksara; Herman Nirwana (Universitas Negeri Padang, 2019)
The problem in this research is the low motivation to learn students, especially male students. This objective of the research is to find out to find out the differences in learning motivation between male and female students of SMAN 1 Bayang Academic Year 2017/2018. This research is comparative research. This research was conducted at SMAN 1 Bayang. This sampling technique is in proportionate stratified random sampling of 150 people. Data analysis techniques are using the t test (independent sample t test). The results of the analysis show that the average learning motivation of male students (Study at Senior High School 1 Shadow) 2017/2018 Academic Year is 88,613. The average learning motivation of female students (Study at SMAN 1 Bayang) 2017/2018 Academic Year is 94,493. There are differences in learning motivation between male and female students (Study at Senior High School 1 Shadow) Academic Year 2017/2018, where the motivation of female students is better than the motivation of male study